2020
DOI: 10.1055/s-0040-1712521
|View full text |Cite
|
Sign up to set email alerts
|

Revision Total Hip Arthroplasty in Osteogenesis Imperfecta

Abstract: Osteogenesis imperfecta (OI) is a rare group of connective tissue disorders commonly associated with bone fragility, deformity, and fractures, leading to instability and early osteoarthritis. Current advancements in the medical and surgical management of OI have extended the life span of these patients, resulting in an increased need for joint arthroplasty to help maintain quality of life. However, surgery among this patient population is technically challenging and comes with a high burden of revision. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Nishida et al demonstrated the use of custom implants in the setting of existing hardware 10 . The use of intraoperative fluoroscopy is an adjunct to aid the surgeon in the setting of a pseudocanal 12 . Corrective valgus and shortening osteotomies have been reported to correct the distorted femoral anatomy in order to allow for femoral component implantation 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Nishida et al demonstrated the use of custom implants in the setting of existing hardware 10 . The use of intraoperative fluoroscopy is an adjunct to aid the surgeon in the setting of a pseudocanal 12 . Corrective valgus and shortening osteotomies have been reported to correct the distorted femoral anatomy in order to allow for femoral component implantation 12,13 .…”
Section: Discussionmentioning
confidence: 99%